Numerical study of pipeline wall thickness influence on natural dynamic parameters of hydromechanical system - А. А. Sekacheva; L. G. Pastukhova; А. S. Noskov (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
This article is devoted to solving the problem of noise and vibration in complex pipelines of hydromechanical systems. In the study, the first ten frequencies of natural oscillations are calculated for sections of the pipeline system filled with water with outer diameters of 60, 70, 102 mm and various thicknesses of the pipeline wall. It is determined that for all the investigated diameters, a decrease in the natural vibration frequencies for all modes of natural vibrations with an increase in the thickness of the pipeline wall is characteristic. Thus, the assumption is confirmed that an increase in the rigidity of the pipeline reduces the likelihood of oscillations in the pipeline. It is concluded that in straight sections the pipeline system with diameters up to 102 mm behaves only as a mechanical system.